A facile route to synthesise silica shell free silicide nanowires - Li, Shaozhou (2013)
We report a new synthesis route to form single-crystalline silicide nanowires (NWs) with the assistance of the reaction between SiO2 and Na2O, which has been intensively studied by glass industry for a century. Rare earth silicide NWs epitaxially grown on the clean silicon substrate surface has been well studied while the synthesis of out-of-plane grown rare earth silicide NWs has not been reported before. In this contribution, we demonstrate that by controlling the growth conditions, it is possible to obtain rare earth silicide NWs that were grown epitaxially aligned or free-standing on silicon wafers. The characterizations show that the NWs are catalyst and silica shell free. The growth mechanism was discussed and electrical properties of the obtained silicide NWs were characterized. These NWs are very attractive nanoscale building blocks for interconnects and fully silicided (FUSI) gate applications in nanoelectronics.